Utilization of Augmented Reality in Facilitating Geography Learning to Improve Spatial Ability of Junior High School Students - Hilmawan Wibawanto; Iwan Maulana (Universitas Negeri Surabaya, 2025)
Spatial ability is a crucial skill in geography education at the junior high school level; nevertheless, some pupils struggle to comprehend abstract spatial concepts due to the constraints of traditional learning medium. Augmented Reality (AR) serves as a novel solution by offering immersive and contextually interactive 3D visuals. This study seeks to elucidate the application of augmented reality media in geography education and evaluate its impact on enhancing students' spatial skills. The employed research methodology is descriptive qualitative, utilizing a case study approach in two private junior high schools located in Surakarta. Data were gathered via classroom observations, comprehensive interviews with educators and students, and documentation, thereafter analyzed employing the Miles and Huberman framework. The findings indicated that augmented reality was executed in three phases: conceptual inquiry, interactive dialogue, and spatial contemplation. Students demonstrated significant enthusiasm and advancements in spatial orientation, cognitive representation, and comprehension of inter-regional relationships. The challenges encountered comprised insufficient devices, unreliable internet connectivity, and pupils' inadequate early digital literacy. This study suggests that augmented reality is not merely a visual-assistance, but also a potent transformative learning medium for enhancing students' spatial skills. The implication is that the incorporation of AR must be supported by teacher training and infrastructure to ensure its best application in geography education.